Production Of Planting Stock From Kacip Fatimah [Labisia Pumila (Bi.) F.Vill & Neves] Through Cuttings - Zahari, Rozihawati (2008)

(untitled)
Labisia pumila (Bl.) F.Vill & Naves (Myrsinaceae) has been traditionally used by Malay women in parturition. Three different varieties of this species were identified and found in Malaysia: viz pumila, alata and lanceolata. However, two of its varieties i.e pumila and alata have been commonly used in traditional medicine and researched as they are more readily available than lanceolata. The increase in logging activities and encroachment in forests caused a decline in the production of L. pumila from its natural stands. This problem is further aggravated by its slow growth in natural forests. Moreover, it is difficult to obtain planting material from the wild. In order to address the demand of L. pumila, it is necessary to find alternative methods of production, specifically vegetative propagation by cuttings, to ensure regular supply of its planting stock. This study aims to explore the possibility of mass producing L. pumila using different propagation systems (misting and non misting), plant parts (stem, petiole and leaf) of two varieties (alata and pumila) and rooting media (river sand, sawdust and 1:1 v/v mixture of river sand and sawdust). This study utilized a Strip-Split Plot (SSPD) in a Randomised Complete Block Design (RCBD). This experiment was conducted in FRIM, Kepong’s, nursery. Results after three months propagation indicated that there were significant differences in all treatments with regards to root and shoot growth. Cuttings of var. alata produced better than var. pumila in terms of root and shoot growth. Propagation in misting systems produced cuttings with higher rooting ability (84%) compared to the ones in non-misting system (72%). However, cuttings in the non-misting system showed higher shooting ability (28%). Cuttings grown in 100% river sand produced higher root and shoot abilities (87% and 26%) than those raised on mixture of 1:1 river sand and sawdust (76% and 24%) and sawdust alone (72% and 23%). Propagation using stem cuttings were found to be the best compared to leaf and petiole cuttings. Based on the elongation of root cells, stem cuttings of variety alata was found to be better than pumila. The elongation of root cell cuttings in those three media, showed a young root primordium elongated through the cortex from parenchyma phloem cell. These root cells were bigger size grown on sawdust and mixture of river sand and sawdust compared to river sand alone. Again, stem cuttings showed the best growth performance than the other plant parts based on height and diameter. In addition, upon chemical analysis of these cuttings, the flavonoids and resorcinol-derivatives content increased in mother plant of var. alata. However, stem rooted cuttings of var. alata had decreased in resorcinol-derivatives, which means it will give less adverse effects to humans compared to var. pumila cuttings. The results of this research demonstrated that L. pumila var. alata stem cuttings could be possibly propagated vegetatively through rooting of cuttings with favorable treatments such those raised on river sand medium under the misting propagation system.